Diversity of Arbuscular Mycorrhizal (AM) Fungal Species from Iron Ore Mine Wastelands in Goa - Rodrigues, B. F. (Indian Forester, 2000)
The use of AM fungi in afforestation is gaining importance. It is known to increase the uptake of phosphorus, carbon sources and indirectly helps to increase biomass and productivity of the host plants. The aim is the present investigation was to isolate and identify the AM species found in the rhizosphere soils of 15 plant species growing on fairly established iron ore mine dumps. The pH of the reject dumps was found to be 6.02 (0.18) with an EC value of 0.051 (0.012) mS/cm. All the plant macro-and micro-nutrients analysed were in very low levels. Chemical analysis of the mine rejects revealed that the mine rejects show acute deficiency of Nitrogen, Phosphorus, Potassium and other essential macro-and micro-nutrients Electrical conductivity (EC) is very low indicating that there is no likelihood of salinity problems for plant growth. Of the 27 identified species, most frequently occurring species include Glomus fasciculatum, Glomus mosseae, Glomus deserticola, Acaulospora bireticulata, Acaulospora spinosa, Gigaspora margarita and Acaulospora foeveata in that order. The present study reveals that there is rich diversity of AM fungi in the fairly established iron ore mine sites, thereby showing promise towards future revegetation programme of the iron ore mine wastelands in Goa State.